Women’s Entrepreneurial and Social Agency in Driving Community-Based Economic Development - Kelechi Tunde; Obinna Ayodele; Ifeanyi Emeka (Journal Social Humanity Perspective, 2026)
This study explores The Role of Women in Social and Economic Development in Nigeria through a qualitative lens, focusing on how women contribute as agents of transformation within communities, institutions, and the broader economy. Drawing on in-depth interviews, field observations, and documentary analysis, the research reveals that Nigerian women play pivotal roles in entrepreneurship, education, healthcare, and social leadership areas that collectively underpin national development. The findings demonstrate that women’s engagement extends beyond domestic and informal sectors, functioning instead as a critical strategic force that drives innovation, economic diversification, and social stability. However, systemic barriers such as limited access to credit, restrictive property rights, and institutional gender bias continue to undermine their potential. The study argues that management systems and development policies must reconceptualize women’s participation not as a welfare or equality issue but as a strategic component of national economic planning. It calls for gender-sensitive management frameworks that integrate women’s contributions into organizational strategy, human capital development, and governance reform. By repositioning women as central to economic and social policy, the study advances the theoretical discourse on inclusive management and provides practical recommendations for policymakers, private sector leaders, and development practitioners. Ultimately, it asserts that achieving sustainable development in Nigeria requires systemic institutional transformation that recognizes and amplifies women’s agency as a cornerstone of national progress.